Students’ perceptions of learning object for3D character modelling lesson - Syamila-Zakiah A.Wahab; Abdul-Nasir Zulkifli; Nurul Fathihin Mohd Noor Shah; Juliana-Aida Abu Bakar; Nur Fadziana Faisal Mohamed; Adzira Husain (2024)
Lecturers have to spend a lot of time to teach their students on the proper techniques of designing and modelling of 3D characters. It is almost impossible for lecturers to cover everything in the class due to the complexities and time-consuming of the procedures and steps. Thus, students have to continue and complete the tasks on their own outside class hours without lecturer’s supervision. Outside the class, students still require some form of instructions that are able to provide them step-by-step procedures of designing and modelling of 3D characters. The instructions must be easy to follow, step-by-step, readily accessible anywhere and anytime. Learning object (LO) is any entity that may be used for learning, education and training. It leads education with the instructional technology towards more effective instructional design, development and delivery of learning content. It provides a new paradigm in the way people teach and learn. In this study, LO has been used for developing students’ 3D design and modelling skills. This paper reports on a perception study among a class of digital arts students of Tuanku Syed Sirajuddin Polytechnic in Perlis, towards the use of LO in 3D Character Modelling lesson. The purpose of this LO is to help students by providing guidance for them to do their assignments and also to enhance and improve their 3D design and modelling skills. An evaluation on the use of the 3D Character Modelling LO was conducted among 30 students. The results indicate that the students agreed on the Learnablity, Usefulness, Ease of Use, Functionality and Effectiveness, Satisfaction and Outcome/Future Use of the LO. The potential use of 3D Character Modelling LO for teaching and learning is discussed at the end of this paper.